Age of attainment of menarche and factors affecting it amongst school girls of Gangtok, Sikkim, India - Pandey, Madhulata; Pradhan, Ashish (International Journal of Contemporary Pediatrics, 2017)
Background: Studies have shown trends of decreasing age at menarche in most of the Indian states. However, there are no such studies reported from the state of Sikkim. Methods:It was a cross sectional prospective study done in four school across Gangtok town. 430 menstruating girls between the age group 10-19 years were the participants. Data regarding chronological age, menstrual age, diet, mother’s age at menarche and socioeconomic status was collected using self-administered pre-tested questionnaire from the girls and their parents. Height, weight and general physical examination of the girls were done. Results: Mean age of attainment of menarche was 12.52 years. 3% girls were undernourished and 20.70% girls had their body mass index more than 85th percentile. A positive correlation between age of onset of menarche with height (r = 0.282), weight (r = 0.130) and mothers age at menarche (r = 0.549) and negative correlation with body mass index (r = -0.155). Menarche was earlier in girls belonging to lower socioeconomic classes (P <0.001). Peak incidence of menarche was noticed in winter months in this hilly area. Diet, ethnicity and sibling order did not show statistically significant effect. Conclusions:The mean age of menarche in this region is comparable to many Indian states. The major determinant of age at menarche in this study was body mass index and mother’s age at menarche similar to other Indian and international studies. Further similar studies on girls from other parts of Sikkim are needed for scientific data.